1996
DOI: 10.1111/j.1365-2990.1996.tb01111.x
|View full text |Cite
|
Sign up to set email alerts
|

Drainage of CSF through lymphatic pathways and arachnoid villi in sheep: measurement of 125l‐albumin clearance

Abstract: We investigated lymphatic drainage pathways of the central nervous system in conscious sheep and quantified the clearance of a cerebrospinal fluid (CSF) tracer into lymph and blood. In the first group of studies, 125I-HSA was injected into the lateral ventricles of the brain or into lumbar CSF and after 6 h, various lymph nodes and tissues were excised and counted for radioactivity. Multiple lymphatic drainage pathways of cranial CSF existed in the head and neck region defined by elevated 125I-HSA in the retro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
81
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(90 citation statements)
references
References 24 publications
8
81
0
1
Order By: Relevance
“…5 suggests that CSF is absorbed from the spinal subarachnoid compartment in the neonate as well. Several groups provided evidence for spinal CSF transport into lymphatics (4)(5)(6)11). In adults at least, arachnoid proliferations resembling the villi and granulations of the cranial system have also been described in spinal tissues (22,31,43), although in many cases, these structures were not associated with veins (43).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 suggests that CSF is absorbed from the spinal subarachnoid compartment in the neonate as well. Several groups provided evidence for spinal CSF transport into lymphatics (4)(5)(6)11). In adults at least, arachnoid proliferations resembling the villi and granulations of the cranial system have also been described in spinal tissues (22,31,43), although in many cases, these structures were not associated with veins (43).…”
Section: Discussionmentioning
confidence: 99%
“…The development of mathematical and tracer methods to estimate lymphatic CSF transport (2)(3)(4)(5), the assessment of the relationship between intracranial pressure and cervical lymph flow (1,42), and the results of intervention experiments in which the lymphatic pathways have been physically obstructed (35,41) have led to the conclusion that a significant volume of CSF transport occurs into extracranial lymphatic vessels in the adult. Indeed, under some conditions, there is evidence that the cribriform-lymphatic route may be the dominant pathway for CSF clearance (35).…”
mentioning
confidence: 99%
“…Most studies with viral vectors have indicated that ependymal and meningeal tissues are effectively targeted but penetration of the viral particle into the parenchyma is highly restricted. Although the flow of CSF has been shown to efficiently clear macromolecules, several studies have indicated that small residual amounts may remain within the perivascular space surrounding the pial arteries and arterioles and may be associated with antigen presenting cells such as macrophages (Kida et al, 1993;Boulton et al, 1996;Harling-Berg et al, 1999). Small "pockets" of virus may exist that serve as a catalyst for local virus production and subsequent trafficking.…”
Section: Can Infectious Virions In the Csf Establish A Local Cns Infementioning
confidence: 99%
“…] Even though we have demonstrated the importance of cervical and prescapular lymphatic vessels in the drainage of gingival tissue, it must noted that these vessels are also responsible for collecting lymph from many other tissues and organs. The cervical lymph, for example, has been shown to drain CNS/CSF (Boulton et al, 1996(Boulton et al, , 1997 as well as other head and neck regions. The prescapular drains a large portion of the animal's neck and upper back.…”
Section: Summary Of Our Findings and The Importance Of Identifying Thmentioning
confidence: 99%